1982
DOI: 10.1007/bf00400382
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics of Aspergillus nidulans mutants defective in carbohydrate metabolism

Abstract: Several mutants aspergillus nidulans defective in carbohydrate metabolism were tested for growth on different carbon sources. D-Galacturonate was found to be a substrate, useful to discriminate between mutants in pyruvate kinase, pyruvate dehydrogenase complex or pyruvate carboxylase. The results of these tests indicate how particular classes of mutants can be obtained and which substrates can be used preferentially for a rapid phenotypical screening of unknown mutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…From Aspergillus nidulans two non-allelic mutants were described that displayed no or very poor growth on GalA (Uitzetter et al, 1982) and an alternative non-phosphorolytic pathway leading to glyceraldehyde and pyruvate was proposed. Furthermore, a specific NADPH dependent glycerol dehydrogenase has been proposed to be involved in the further conversion of D-glyceraldehyde to glycerol (Sealy-Lewis and Fairhurst, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…From Aspergillus nidulans two non-allelic mutants were described that displayed no or very poor growth on GalA (Uitzetter et al, 1982) and an alternative non-phosphorolytic pathway leading to glyceraldehyde and pyruvate was proposed. Furthermore, a specific NADPH dependent glycerol dehydrogenase has been proposed to be involved in the further conversion of D-glyceraldehyde to glycerol (Sealy-Lewis and Fairhurst, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…There are a few studies on the D-galacturonic acid path in the mold Aspergillus nidulans. Mutants which were not able to utilize D-galacturonate were identified as transaldolase and pyruvate dehydrogenase mutants (6). In a later work, it was shown that a mutant defective in pyruvate dehydrogenase could not grow on D-galacturonic acid whereas a mutant defective in pyruvate kinase could grow.…”
mentioning
confidence: 99%